The intra-industry trade of Mexico with its main trading partners - Buitelaar, Rudolf M.; Padilla, Ramón (Estudios Económicos de El Colegio de México, 1996)
This article analyzes the degree of intraindustry trade of Mexico with its main trading partners, on the basis of official data at the 4-digit level of the Harmonized System for the years 1990-1995. Data are presented per region and product. It is found that this type of trade represents over 40% of Mexico's total foreign trade. The analysis reveals a correlation between the volume of trade and the degree of intraindustry trade, and establishes a positive relation between the latter indicator and the existence of free trade agreements. A formula is introduced to calculate the triangulation of trade.